2021
DOI: 10.1097/md.0000000000025758
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of osteopenia of prematurity in preterm infants without phosphate supplementation

Abstract: To meet their requirements for bone mineralization, it is recommended that preterm infants receive nutritional support containing calcium and phosphate. There are no clear data on the incidence of osteopenia of prematurity (OFP) in preterm infants without phosphate supplementation. This study aimed to investigate the incidence of OFP in preterm infants without phosphate supplementation and its relationship with the duration of parenteral nutrition (PN). This was a prospective and observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
2
9
0
1
Order By: Relevance
“…The rate of MBD found in our population reflects what is reported in the literature, i.e., 22% VLBWI with gestational age < 32 weeks are at an increased risk of developing MBD during hospital stays [10,[20][21][22][23]. This is probably a consequence of the fact that the highest bone mineralization occurs in the last trimester of pregnancy, and that intrauterine growth retardation may be associated with placental dysfunction, and therefore a reduction in nutrient supply from mother to fetus [2,25].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The rate of MBD found in our population reflects what is reported in the literature, i.e., 22% VLBWI with gestational age < 32 weeks are at an increased risk of developing MBD during hospital stays [10,[20][21][22][23]. This is probably a consequence of the fact that the highest bone mineralization occurs in the last trimester of pregnancy, and that intrauterine growth retardation may be associated with placental dysfunction, and therefore a reduction in nutrient supply from mother to fetus [2,25].…”
Section: Discussionsupporting
confidence: 83%
“…A total of 289 VLBWIs were enrolled in the present study; 51 infants died during the first six weeks of life (mean days of life at death was 10.27 ± 7.5 days, range 1-31), so 238 subject with a mean gestational age of 29.2 ± 1.98 weeks and mean birth weight of 1131.13 ± 258.20 g were included in the final analysis (male 45%, twins 51%). According to serum P and ALP concentration performed at 25.84 ± 3.45 days of life [19][20][21][22][23][24][25][26], subjects were divided into two groups: G1 (=52 subjects) infants were at increased risk of MBD as they had P ≤ 4.5 mg/dl or ALP ≥ 900 UI/L, while G2 (=186 subjects) infants did not have an increased risk of MBD. Table 1 reports clinical data in G1 and G2.…”
Section: Resultsmentioning
confidence: 99%
“…The study showed an incidence of 40% of the disease, which is within the range reported in the literature. Although it is suggested that early diagnosis based on biochemical tests may overestimate cases of osteopenia, our result corroborates a recent study by Angelika et al [ 39 ], which found 43% of newborns with the disease, diagnosed by imaging tests, highlighting its importance as an incident comorbidity in preterm newborns, regardless of the screening method.…”
Section: Discussionsupporting
confidence: 91%
“…The incidence of MBDP is inversely related to the birth weight and gestational age. Previous studies have identified the incidence as high as 10% of low-birth-weight babies (LBW) less than 2500 g, 20% of very-low-birthweight (VLBW) babies -less than 1500 g and 30-60% of extreme low-birth-weight (ELBW) babies less than 1000 g 2,6]. Despite guidelines from the American Academy of Pediatrics Committee on Nutrition since 2013 [3], there continues to exist a wide variety of approaches to screening and managing MBDP across NICU centers [7].…”
Section: The Problemmentioning
confidence: 99%